Navigating Marginality: Identity Construction and Resistance among GEMAPAKTI DIY - Ginting, Eikel Karunia (Indigenous Southeast Asian and Ethnic Studies, 2025)
This study examines the identity construction of GEMAPAKTI DIY, a youth organisation for adherents of indigenous religions in Yogyakarta, Indonesia, within the context of persistent marginalisation. Despite constitutional recognition, indigenous religious groups continue to experience systemic discrimination due to the state’s exclusionary approach to religious diversity. Limited access to education, employment, and public participation presents significant barriers for GEMAPAKTI DIY members. Employing a qualitative methodology, this study utilises in-depth interviews to gain a comprehensive understanding of their lived experiences. Data collection prioritises informants’ perspectives, providing nuanced insights into identity formation. The data is systematically described, categorised, and interpreted, with theoretical frameworks guiding the analysis to ensure a structured understanding. The findings indicate that GEMAPAKTI DIY constructs its identity through internal consolidation, social media advocacy, filmmaking, and collaboration with NGOs and academic institutions. These strategies function as forms of resistance against structural and social marginalisation while fostering a sense of solidarity among young indigenous religion adherents. Applying Manuel Castells’ identity formation theory, this study identifies GEMAPAKTI DIY’s efforts as an example of “project identity,” whereby marginalised groups actively redefine their presence in public discourse. This paper argues that achieving an inclusive religious democracy in Indonesia necessitates systemic policy reforms, including bottom-up approaches, multicultural education, and full governmental recognition of indigenous religions. Cross-sector collaboration is essential to ensuring equal rights and opportunities, thereby fostering a participatory democracy that upholds religious freedom for all.